The surgical strategy for multilevel massive ossification of the posterior longitudinal ligaments - Li, Ying-Ching; Liu, Zhuo-Hao; Li, Ying-Sheng; Yeap, Mun-Chun; Liu, Yu-Tse; Huang, Yin-Cheng; Chen, Ching-Chang; Tu, Po-Hsun (Frontiers in Surgery, 2022)
Purpose Creating enough decompression, favorable outcome, less complication, and maintain adequate lordosis and stability in the patients with cervical myelopathy due to multilevel massive ossification of the posterior longitudinal ligament (OPLL) still poses a challenge for surgeons. The aim of our study is to retrospectively evaluate our patients and try to seek a better surgical strategy. Methods Between 2015 and 2019, 55 consecutive patients with multilevel massive OPLL underwent surgical treatment. Among these, 40 patients were treated with cervical laminectomy and then anterior decompression, fusion, and fixation (ADF), which was defined as group 1, and 15 patients were treated with cervical laminectomy and fixation simultaneously, which was defined as group 2. The patient's radiographic characteristics and postoperative outcomes were evaluated. Results Better postoperative cervical sagittal lordosis and less long-term axial pain was achieved in group 1 (p < 0.001), though the functional outcome had no significant difference. In the multivariable analysis, anterior fixation accounts for independent factors for better cervical sagittal alignment (p < 0.001). No complications directly associated with cervical laminectomy were observed. Conclusion In patients with cervical multilevel massive OPLL, laminectomy at compression level and then ADF depended on the severity and range of compression, but corpectomy of not more than two vertebral bodies is suggested, except K-line (+) and long-segment massive OPLL majorly involving the C2 and posterior laminectomy above and below the OPLL-affected levels with posterior fixation simultaneously.